2015
DOI: 10.1111/jace.13418
|View full text |Cite
|
Sign up to set email alerts
|

Microwave Dielectric Properties of a Low‐Firing Ba2BiV3O11 Ceramic

Abstract: A low‐firing microwave dielectric ceramic Ba2BiV3O11 was prepared via solid‐state reaction method. Ba2BiV3O11 ceramic could be well sintered at 840°C–880°C, with a εr ~14.2, a high Q × f value ~68 700 GHz (at 8.7 GHz), and a negative temperature coefficient of −81 ppm/°C. τf of Ba2BiV3O11 was tuned to be near zero by formation of a composite with TiO2. 0.7Ba2BiV3O11–0.3TiO2 ceramic sintered at 910°C showed improved properties with εr = 15.7, Q × f = 53 200 GHz, and τf  = −2 ppm/°C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…For the application of microwave dielectric ceramics, a near‐zero τ f value is needed . In general, some positive τ f value materials, such as TiO 2 and CaTiO 3 , are utilized as compensation materials for negative τ f value materials to acquire a near‐zero τ f value.…”
Section: Resultsmentioning
confidence: 99%
“…For the application of microwave dielectric ceramics, a near‐zero τ f value is needed . In general, some positive τ f value materials, such as TiO 2 and CaTiO 3 , are utilized as compensation materials for negative τ f value materials to acquire a near‐zero τ f value.…”
Section: Resultsmentioning
confidence: 99%
“…Among them, Ba 2 LaV 3 O 11 has attracted extensive attention in recent years due to its excellent microwave dielectric properties (ε r = 12.8, Q × f = 31 800 GHz, and τ f = −14.0 ppm/°C), and low sintering temperature (840°C) . We also found that Ba 2 BiV 3 O 11 ceramic could be densified at 870°C and possessed good microwave dielectric properties with ε r = 14.2, Q × f = 68 700 GHz, and τ f = −81.0 ppm/°C . This stimulates us to investigate whether other compounds in Ba 2 LnV 3 O 11 system exhibit good microwave dielectric properties.…”
Section: Introductionmentioning
confidence: 75%
“…An important factor which influences the dielectric constant in microwave dielectric ceramics is the average ionic polarizability (α theo / V m ) . And it can be determined by the modified Clausius‐Mossotti equation as follows:…”
Section: Resultsmentioning
confidence: 99%